2016
DOI: 10.1002/mrc.4424
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and composition of crude oil by low‐field nuclear magnetic resonance

Abstract: Nuclear magnetic resonance (NMR) techniques are widely used to identify pure substances and probe protein dynamics. Oil is a complex mixture composed of hydrocarbons, which have a wide range of molecular size distribution. Previous work show that empirical correlations of relaxation times and diffusion coefficients were found for simple alkane mixtures, and also the shape of the relaxation and diffusion distribution functions are related to the composition of the fluids. The 2D NMR is a promising qualitative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…By choosing an appropriate pulse sequence, the signal intensity of samples can be reflected in terms of the T 1 and T 2 relaxation times obtained from Carr‐Purcell‐Meiboom‐Gill (CPMG) and inversion recovery (IR) sequences, respectively (Nakayama et al., 2015). Results of preliminary experiments showed that in terms of performance, T 2 relaxation time was better than that of T 1 relaxation because of “lipid‐water separation” studied in a previous report (Jia et al., 2016). Thus, T 2 measurement has been utilized for further study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By choosing an appropriate pulse sequence, the signal intensity of samples can be reflected in terms of the T 1 and T 2 relaxation times obtained from Carr‐Purcell‐Meiboom‐Gill (CPMG) and inversion recovery (IR) sequences, respectively (Nakayama et al., 2015). Results of preliminary experiments showed that in terms of performance, T 2 relaxation time was better than that of T 1 relaxation because of “lipid‐water separation” studied in a previous report (Jia et al., 2016). Thus, T 2 measurement has been utilized for further study.…”
Section: Methodsmentioning
confidence: 99%
“…Low‐field 1 H Nuclear magnetic resonance (LF‐ 1 H NMR) technique is a rapid, non‐destructive, highly reproducible, and sensitive technique (Hazlett et al., 1999; Seton, Hutchison, & Bussell, 1997), and has successfully been applied in quality control of food products such as porcine muscle (Qin, Xu, Zhou, & Wang, 2015; Shao, Deng, Jia, et al., 2016; Shao, Deng, Song, et al., 2016), pork (Shao, Deng, Jia, et al., 2016; Shao, Deng, Song, et al., 2016), salmon (da Silva Carneiro et al., 2016), crude lipid (Barbosa, Sad, Morgan, Figueiras, & Castro, 2016; Jia et al., 2016), egg (Zhao et al., 2016), milk (Salomonsen, Sejersen, Viereck, Ipsen, & Engelsen, 2007), honey (Ribeiro et al., 2014), and cod (Gudjónsdóttir, Arason, & Rustad, 2011). The LF‐ 1 H NMR technique is often employed to investigate the water mobility and/or lipid content of foods because it can measure water or lipid proton relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalteneeasily aggregates with other molecules to produce a supramolecular structure. This aggregate will slow down molecular motion, which can be detected by measuring T 1 -T 2 distribution (Jia et al 2016). 10 -2 10 -1 10 0 10 1 Signal amplitude 10 -1 10 -2 10 -3 10 -3 10 -2 10 -1 10 0 10 1 (b) Fig.…”
Section: Oil Molecular Dynamics and Compositionmentioning
confidence: 99%
“…The first step is to enhance the understanding of multiple relaxation mechanisms related to rock components and pore structures. For instance, prominences including composition diversity, storage, and seepage dominated by nanoscale pores and throats, and coexisting multi-scale pores, make relaxation mechanisms in shales more complex (Washburn and Birdwell 2013;Daigle et al 2014;Jia et al 2016Jia et al , 2017 Washburn and Cheng 2017): (1) Organic matter affects fluid NMR signal, and dipole-dipole coupling between 1 H atoms is the controlling factor. (2) The distribution and compaction of clay influence NMR responses, and clay's type and components will affect the wettability of pores and adsorption of water molecules.…”
Section: Improvement Of Theories and Modelsmentioning
confidence: 99%